Isolation and Characterization of Lytic Bacteriophages from Wastewater with Phage Therapy Potentials Against Gram-Negative Bacteria - Khorshidtalab, Mona; Durukan, Inci; Tufekci, Enis Fuat; Nas, Seyran S.; Abdurrahman, Mujib A.; Kilic, Ali O. (AVES YAYINCILIK A.Ş., 2022)
The increase of multidrug resistance in bacteria has increased the efforts in search of alternative methods. The aim of the present study was to isolate and characterize the lytic phages and assess their lytic activity against a number of gram-negative bacteria.The phages and their respective hosts were isolated from wastewater collected from the municipal sewer system of Trabzon, Turkey. The lytic activities of phage were determined using the agar spot test. The identification and antibiotic susceptibility of host bacteria were determined using matrix-assisted laser desorption ionization time-of-flight mass spectrometry and Phoenix 100, respectively. The phages were characterized morphologically using transmission electron microscopy. One of the phages, Enteroc21, which has a broad-host-range, was further characterized by genome restriction endonuclease analysis and burst size.Two phages infected strains of four different species, nine phages were able to infect 2-4 strains belonging to one or two species, and three phages showed lytic activity against only the hosts from which they were isolated. All phages belonged to the Siphoviridae, Myoviridae, and Podoviridae family based on trans- mission electron microscopy morphology. The Enteroc21 had more than 100 kb genome size and a burst size of 180 per infected cell. Most of the host strains were resistant to ampicillin, amoxicillin-clavulanic acid, and in particular, Achromobacter xylosoxidans TRAX 13 was multidrug-resistant showing resistance to cefepime, aztreonam, gentamicin, netilmicin, and ciprofloxacin.This study showed that the isolated phages have the potential to be used in phage therapy against various bacterial infections, including multidrug-resistant bacteria.
Keywords: Medicine (General); Original Article Microbiology and Clinical Microbiology; R5-920; 6. Clean water; 3. Good health